Adipose-derived stem cells alleviate radiation-induced muscle fibrosis by promoting muscle regeneration - Li, Sha; Peng, Mingjing; Ou, Xiang; Zhou, Zhijiao; Xie, Luyuan; Ge, Yuxin; Song, Zehong; Zhou, Xiao; Shi, Chunmeng; Sheng, Xiaowu (Frontiers in Cell and Developmental Biology, 2025)
BackgroundRadiation-induced muscle fibrosis (RIF) is a severe late-stage side effect of radiotherapy in adjacent normal tissues, significantly affecting anticancer therapeutic efficacy and potentially being life-threatening. Previous studies have shown that satellite cells (SCs) become activated after ionizing radiation to facilitate muscle tissue repair. However, the acceleration and strengthening of this process have received little attention until recently. Adipose-derived stem cells (ADSCs), a type of mesenchymal stem cell, have emerged as a promising therapeutic option in regenerative medicine due to their accessibility, abundance, and plasticity in adult organisms. In this study, we explored whether ADSCs could enhance SC proliferation and differentiation after radiation therapy.MethodsADSCs were harvested, cultured, and passaged from male Sprague–Dawley rats and characterized in vitro. In vivo, rats were randomly assigned to control and ADSC-treated groups (n = 6). ADSCs were transplanted into RIF rat models at different time points (4, 12, and 24 w). The therapeutic effects of transplanted ADSCs were assessed via Masson’s trichrome staining, electron microscopy, and hematoxylin–eosin (H&E) staining. SC activation, proliferation, and central nuclear immigration following ADSC transplantation therapy were evaluated via real-time polymerase chain reaction and H&E staining.ResultsIn vivo, fibrosis was markedly alleviated over time following ADSC treatment. In the RIF rat model, ultrastructural histopathological changes, including mitochondrial edema and vacuolization, myofilament dissolution, and vascular endothelial swelling, were notably attenuated by ADSC transplantation. Additionally, SCs exhibited a significant increase in activation and proliferation in the ADSC-treated groups, accompanied by a decrease in fibrotic symptoms.ConclusionOur study provides evidence that ADSCs protect against RIF by promoting SC activation, proliferation, and differentiation in vivo. ADSCs may represent a promising therapeutic candidate for restoring muscle dysfunction and abnormalities caused by RIF.